A blue dive: from 'blue fingers' to 'blue silver'. A comparative overview of staining methods for in-gel proteomics. (December 2012) - Panfoli, Isabella; Calzia, Daniela; Santucci, Laura; Ravera, Silvia; Bruschi, Maurizio; Candiano, Giovanni
Gel-based proteomics are the most useful method for protein separation, even when compared with gel-free proteomics. Proteomic analysis by 2D gel electrophoresis (2-DE) with immobilized pH gradients is in turn the best approach to large-scale protein-expression screening. Spots visualization is pivotal for protein identification by mass spectrometry. Commonly used staining methods with excellent mass spectrometry compatibility are coomassie brilliant blue (CBB) or fluorescent dyes. In this study, an implementation of 'blue silver' colloidal CBB staining, characterized by high sensitivity and immediate low background, is discussed. The sensitivity of classical, colloidal and 'blue silver' CBB staining methods was compared on monodimensional and 2-DE gels. The implementation of the 'blue silver' method performs better, provided the physical state of the micelles is respected. An example of a 2-DE of human urine treated with combinatorial peptide ligand libraries demonstrates that implemented 'blue silver' can evidence the complexity of the sample.